PENGARUH PERMAINAN DAKON TERHADAP MATHEMATICS SELF EFFICACY SISWA KELAS II SD MUHAMMADIYAH AMBARBINANGUN KASIHAN BANTUL - Zashinta, Icco (Jurnal PGSD Indonesia, 2021)
AbstractÂ This study aims to determine the effect of the application of traditional dakon games on the mathematics self-efficacy of second grade students of SD Muhammadiyah Ambarbinangun Kasihan Bantul. At this time, teachers have not maximized the use of learning media, especially in learning mathematics, so that students find it difficult to understand the material and become less confident in their mathematical abilities.This research is a quasi-experimental research (Quasi Experimental Design) using control class and experimental class as research subjects. The data collection technique used is a questionnaire. The results of the questionnaire were tested using the independent sample t-test to determine the effect of the dakon game on mathematics self-efficacy.Based on the results of the study, the dakon game has a positive influence on the mathematics self-efficacy of second grade students of SD Muhammadiyah Ambarbinangun Kasihan Bantul. This can be seen from the results of parametric statistical hypothesis testing using the independent sample t-test test on the pretest and posttest questionnaires. In this test, the results of sig. 2 tailed 0.002 which means it is smaller than alpha 0.05 so that the two classes do not have the same average level of mathematics self-efficacy. The control class average pretest and posttest scores remained at 32.55 because they were not treated using the dakon game and the experimental class treated using the dakon game the posttest value increased by 35.90 compared to the pretest value. This means that giving treatment using the dakon game can improve students' mathematics self-efficacy, because the class that is given treatment using the dakon game increases on average compared to the class that is not given the treatment.Keywords: dakon game, mathematics self efficacy, elementary school